Adoption and Use of Learning Management Systems in Education: the Role of Playfulness and Self-Management - Akküçük, Ulaş; Balkaya, Selen (MDPI [Commercial Publisher], 2021)
This article investigates the factors affecting primary and secondary education teachers' behavioral intention to adopt learning management systems (LMSs). Information technology (IT) innovations have the power to change the way we work, educate, learn, and basically the way we live. The effect of IT innovations on education makes it critical to understand the current usage situation of LMSs and the factors affecting their adoption by teachers. The unified theory of acceptance and use of technology (UTAUT) was extended with factors from education and game-based learning literature. In order to see the effect of individual- and organizational-level characteristics, multi-group structural equation modeling (SEM) analysis was conducted and discrepancies in relationships were reported. Evaluation of users and non-users and teachers of different fields were also compared to each other. The findings of this study not only contribute to theory through the development and testing of a thorough model relating technology features and individual characteristics to behavioral intention to use, but also offer strong implications for practitioners who would like to increase LMS usage and create a more effective learning environment.
Keywords: Technology in education; Ttechnology acceptance; Learning management systems; Technology Acceptance